ONLINE LEARNING MANAGEMENT TO IMPROVE STUDENT ACADEMIC ACHIEVEMENT - Pebriana Priyambodo; Fitri Nurmahmudah (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to strengthen the understanding of the importance of managing online learning to improve students' academic achievement in the proper use of the learning model, namely Blended Learning. This research is motivated by the development of 21st-century technology in the world of education that has not been managed optimally by educators, causing students to experience difficulties in participating in applied online learning. This research uses a qualitative method with a case study design. The research subjects were teachers of State Elementary School 2 Sumberagung, Bantul Regency, Yogyakarta. The data collection techniques through interviews. The study results show that online learning management is carried out in systematic and accurate planning, implementation, and assessment stage. The use of the learning model Blended Learning can positively impact students. The evidence is the results of the average academic score during online learning can achieve the Minimum Completence Criteria (KKM). In addition, the average score obtained by students is also stable. The management of online learning evaluation that is carried out correctly and highly committed can improve student academic achievement.